MATHEMATICS LEARNING USES THE PMRI APPROACH TO IMPROVE STUDENT LEARNING OUTCOMES - YANSEN, DEDI (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2024)
This research aims to improve student learning outcomes in learning mathematics data processing materials using the PMRI approach. The research method used is the Demonstration Method. The subject of the study was a grade VI student of SD Negeri 1 Rambang Muara Enim Regency. The learning improvement procedure is done through Classroom Action Research (PTK), which takes two cycles. Each cycle, the activities carried out include (1) Planning, (2) Implementation, (3) Observation, and (4) Reflection. The data collection technique is carried out through observation sheets for each meeting by researchers to see data about learning activities. The results of the analysis of the research data were obtained: In the first cycle, only 64.3% of students completed and 57.1% were actively involved in learning; in the second cycle, the completed students increased to 92.8%, and students who were active in learning 85.7%